2012
DOI: 10.1371/journal.pone.0042460
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effects of an Introduced Palm on a Riparian Invertebrate Community in Southern California

Abstract: Despite the iconic association of palms with semi-arid regions, most are introduced and can invade natural areas. Along the San Diego River (San Diego, California, USA), the introduced Canary Island date palm (Phoenix canariensis) forms dense patches among native riparian shrubs like arroyo willow (Salix lasiolepis). The structural differences between the palm and native shrubs are visually obvious, but little is known about palm’s effects on the ecosystem. We tested for the effects of the palm on a riparian i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…At least some members of these groups would use the structure of I. glandulifera as resting sites without feeding on the plant. When studying the impact of an introduced palm species ( Phoenix canariensis Chabaud) along the San Diego River in California, USA, Talley et al [22] showed that there was no impact of the palm on the ground-dwelling invertebrate community when compared to native stands of willow ( Salix lasiolepis Benth.). What our study and that of Talley et al [22] highlights is that in contrast to the foliage invertebrate community, ground-dwelling invertebrates are not solely reliant on live plants for food and development and so might not be affected by changes in vegetation composition caused by an invasive plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least some members of these groups would use the structure of I. glandulifera as resting sites without feeding on the plant. When studying the impact of an introduced palm species ( Phoenix canariensis Chabaud) along the San Diego River in California, USA, Talley et al [22] showed that there was no impact of the palm on the ground-dwelling invertebrate community when compared to native stands of willow ( Salix lasiolepis Benth.). What our study and that of Talley et al [22] highlights is that in contrast to the foliage invertebrate community, ground-dwelling invertebrates are not solely reliant on live plants for food and development and so might not be affected by changes in vegetation composition caused by an invasive plant.…”
Section: Discussionmentioning
confidence: 99%
“…Below- and ground-dwelling herbivores are more generalist plant feeders compared to foliage herbivores that specialise on one or a number of closely related species [21]. The varying dominance of different functional feeding groups between trophic levels may account for the more pronounced negative response of above-ground invertebrates to the occurrence of a non-native plant species [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in vegetation composition may lead to changes in structural characteristics, including cover, plant height, and concomitant changes in bare ground (e.g., Toft et al 2001;Standish 2004;Spyreas et al 2010). Structural changes may affect arthropod movement and modify temperature, light intensity, and soil moisture, which are important determinants of the distribution and reproductive success of certain arthropod taxa (Wolkovich et al 2009;Schirmel et al 2011;Talley et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Invasive plants also can alter characteristics of the litter and soil (Standish 2004;Kappes et al 2007;Wolkovich et al 2009). Increases in dominance by invasive plants often are associated with increases in the amount and depth of litter and changes in chemical composition of litter, characteristics important for detritivores (Lambrinos 2000;Talley et al 2012;Alerding & Hunter 2013). Invasive plants may contribute to changes in soil nutrients, moisture, salinity, and pH, and these changes may affect reproduction and composition of arthropods belowground (Witkowski 1991;Gratton & Denno 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of displacement of native plants by goldenrod on aphids is unknown. Second, the decline in ant diversity and abundance could be due to changes in microclimatic conditions (temperature, moisture, light intensity) caused by modifications in structural characteristics (increasing cover, plant height) as well as in litter accumulation and in soil characteristics (nutrients, salinity, pH) (Standish 2004;Wolkovich et al 2009;Talley et al 2012), which may be important especially for thermophilic species such as M. scabrinodis.…”
Section: Discussionmentioning
confidence: 99%